2013
DOI: 10.1063/1.4802936
|View full text |Cite
|
Sign up to set email alerts
|

Protein sensing by nanofluidic crystal and its signal enhancement

Abstract: Nanofluidics has a unique property that ionic conductance across a nanometer-sized confined space is strongly affected by the space surface charge density, which can be utilized to construct electrical read-out biosensor. Based on this principle, this work demonstrated a novel protein sensor along with a sandwich signal enhancement approach. Nanoparticles with designed aptamer onside are assembled in a suspended micropore to form a 3-dimensional network of nanometer-sized interstices, named as nanofluidic crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…A label-free technique, which could directly detect the binding of a target protein to the surface antibody would be much more suitable as a point of care diagnostic. Various labelfree nanoelectronic [25][26][27][28] sensors including nanowires have been demonstrated exhibiting femtomolar detection limits. 29 The detection limit or the minimum detectable concentration of target biomarkers in the test sample is dependent on two parameters: the transducer sensitivity (the minimum number of binding events on the sensor surface required to generate sensor response greater than the noise level) and the capture rate of target molecules on the surface of the sensor.…”
mentioning
confidence: 99%
“…A label-free technique, which could directly detect the binding of a target protein to the surface antibody would be much more suitable as a point of care diagnostic. Various labelfree nanoelectronic [25][26][27][28] sensors including nanowires have been demonstrated exhibiting femtomolar detection limits. 29 The detection limit or the minimum detectable concentration of target biomarkers in the test sample is dependent on two parameters: the transducer sensitivity (the minimum number of binding events on the sensor surface required to generate sensor response greater than the noise level) and the capture rate of target molecules on the surface of the sensor.…”
mentioning
confidence: 99%
“…It has been demonstrated that the surface charge dominated the ion conductance of the NPC at low bulk concentration condition, the surface charge density would be changed due to the reaction between the immobilized probe molecule on the nanoparticle and the dissociated target molecule, and the induced conductance variation could be used for sensing the concentration of the target molecule (Lei et al, 2010;Sang et al, 2013).…”
Section: Characterization Of the Nanofluidic Biosensormentioning
confidence: 99%
“…Combining nanofluidic chips with the nanoparticle crystal (NPC) could be one of the effective approaches to the nanofluidic biosensing beacause the surface chemical properties of nanoparticles can be easily tuned. In our previous works, with a glass or silicon chip, the sensing principle, selectivity and specificity of the NPC-based nanofluidic biosensing have been demonstrated (Ouyang et al, 2013;Sang et al, 2013). However, it was found that there were several possible issues for ultra-high sensitive nanofluidic sensing by using silicon or glass as the chip substrate, such as a large background noise, non-transparent substrate (Si), a relatively long and expensive process, etc.…”
Section: Introductionmentioning
confidence: 98%
“…Upon the binding of cocaine, the immobilized aptamers changed to a conformation with less space occupation, which increased the effective radius of the nanochannels and led to the increased ionic fluxes through the nanofluidic crystal. 57 Based on the electrostatic effect, Lei et al 117 and Sang et al 118 demonstrated nanofluidic crystal-based biochemical sensing of biotin and human α-thrombin in low ionic concentrations (<10 −5 M), achieving a similar LOD of ~1 nM. In the work of Sang et al , upon the binding of human α-thrombin to the negatively charged aptamer-modified 540 nm nanofluidic crystal, the surface charge density of the nanoparticles increased, which led to the increase of the conductance of the nanofluidic crystal (Figure 11(a)).…”
Section: Applicationsmentioning
confidence: 99%